Study of CD27, CD38, HLA-DR and Ki-67 immune profiles for the characterization of active tuberculosis, latent infection and end of treatment - Díaz-Fernández, Sergio; Villar-Hernández, Raquel; Stojanovic, Zoran; Fernández, Marco; Galvão, Maria Luiza De Souza; Tolosa, Guillermo; Sánchez-Montalva, Adrián; Abad, Jorge; Jiménez-Fuentes, María Ángeles; Safont, Guillem; Romero, Iris; Sabrià, Josefina; et al. (Frontiers in Microbiology, 2022)
Background: Current blood-based diagnostic tools for TB are insufficient to properly characterize the distinct stages of TB, from the latent infection (LTBI) to its active form (aTB); nor can they assess treatment efficacy. Several immune cell biomarkers have been proposed as potential candidates for the development of improved diagnostic tools. Objective: To compare the capacity of CD27, HLA-DR, CD38 and Ki-67 markers to characterize of LTBI, active TB and patients who ended treatment and resolved TB. Methods: Blood was collected from 45 patients defined according to clinical and microbiological criteria as: LTBI, aTB with less than 1 month of treatment and aTB after completing treatment. Peripheral blood mononuclear cells were stimulated with ESAT-6/CFP-10 or PPD antigens and acquired for flow cytometry after labelling with conjugated antibodies against CD3, CD4, CD8, CD27, IFN-γ, TNF-α, CD38, HLA-DR, and Ki-67. Conventional and multiparametric analyses were done with FlowJo and OMIQ, respectively. Results: The expression of CD27, CD38, HLA-DR and Ki-67 markers was analyzed in CD4+ T-cells producing IFN-γ and/or TNF-α cytokines after ESAT-6/CFP-10 or PPD stimulation. Within antigen-responsive CD4+ T-cells, CD27- and CD38+ (ESAT-6/CFP-10-specific), and HLA-DR+ and Ki-67+ (PPD- and ESAT-6/CFP-10-specific) populations were significantly increased in aTB compared to LTBI. Ki-67 demonstrated the best discriminative performance as evaluated by ROC analyses (AUC>0.9 after PPD stimulation). Data also points to a significant change in the expression of CD38 (ESAT-6/CFP-10-specific) and Ki-67 (PPD- and ESAT-6/CFP-10-specific) after ending the anti-TB treatment regimen. Furthermore, ratio based on the CD27 median fluorescence intensity in CD4+ T-cells over Mtb-specific CD4+ T-cells showed a positive association with aTB over LTBI (ESAT-6/CFP-10-specific). Additionally, multiparametric FlowSOM analyses revealed an increase in CD27 cell clusters and a decrease in HLA-DR cell clusters within Mtb-specific populations after the end of treatment. Conclusions: Our study independently confirms that CD27-, CD38+, HLA-DR+ and Ki-67+ populations on Mtb-specific CD4+ T-cells are increased during active TB disease. Multiparametric analyses unbiasedly identify clusters based on CD27 or HLA-DR whose abundance can be related to treatment efficacy. Further studies are necessary to pinpoint the convergence between conventional and multiparametric approaches.